Escarabeíneos da região de transição cerrado/caatinga: contribuição para fauna de pastagens - Oliveira, Rafaella Teixeira Maciel (2015)
Since our colonization, Brazil has been suffering intense transformations resulting from population growth. The changes in the habitats, especially to the forest fragmentation, comprise the two main landscape modifiers. Among the systems that are most affected by landscape transformation are tropical savannas. However, little is understood about the loss standards of biodiversity of these systems. Due to the huge pressure practiced in the savanna it is possible imagine that the transition regions who exists between this biomes are also very threatened. This is an aggravating in the transition regions has great biodiversity, with species belonging to adjacent systems, as well as unique species of transition areas. Despite its importance studies in transition areas are still rare. In Brazil, one of the most important transition area is the transition Cerrado/Caatinga. Having large areas of this vegetation, Piaui State is in a concern for the conservation of these transition areas. The southwestern region of the state has been developing rapidly due to the large agricultural expansion and livestock that exist in the region. A group that has often been used is the dung beetles that’s belongs to the subfamily of Scarabaeinae, since the dung beetles are a good tool to comprehend the effects of the soil changes. The transition areas that are little known, suffer great pressure from expansion of agriculture and livestock. This study aims: evaluate the impacts caused by changes of the soil use by dung beetles communities in the transition area Cerrado / Caatinga and evaluate what the best type of pasture management.